A Hilbert-type integral inequality on the fractal space. Issue 10 (3rd October 2017) - Liu, Qiong; Chen, Dazhao
ABSTRACT: Based on the local fractional calculus, by using the methods of weight function, a Hilbert-type fractal integral inequality and its equivalent form are given. Their constant factors are proved being the best possible, and its applications are discussed briefly.